Using Guided Questions Technique (GQT) to Improve Students Writing Skill - Desti Sri Wahyuni; Afrillia Aggreni; Jamiluddin, Jamiluddin; Mochtar Marhum (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The Guided Question Technique (GQT) has recently caught the interest of researchers. Although many studies have explored the effects of GQT on skills like reading and speaking, there are relatively few investigations into its impact on students' writing abilities, specifically in crafting descriptive texts. This paper aims to examine whether the guided question technique (GTQ) can enhance students' writing skills, specifically in composing descriptive texts. To achieve the study's objective, seventy students from SMA Negeri 7 Palu in Indonesia were purposively divided into two groups. One group received treatment from a researcher, while the other did not. The findings demonstrated a notable distinction between the treated and untreated groups. Students who received the treatment performed better in writing descriptive texts than those who did not. The results of this study clearly showed that employing the guided question technique in teaching writing skills was advantageous for intermediate-level students in writing descriptive texts. These findings have implications for teacher and other researchers.